Study on the shear movement law of overlying strata by slice mining. Issue 7 (3rd March 2020) - Fu, Junhui; Wen, Guangcai; Sun, Haitao; Yang, Xuelin
Abstract: Based on the analysis of shear movement characteristics of overlying strata under mining effect, a quantitative calculation model for shear displacement in the along‐strike and down‐dip directions of the overlying strata is established. The shear displacement at any point on the interface of overlying strata in composite rock beam under slice mining is analyzed. The evolution law of shear displacement and deformation of the overlying strata with the advancement of working face was inverted by physical simulation test. The results show that the shear movement of the overlying strata is characterized by a repeated pattern of "increase → decrease →increase → decrease." The shear displacement of the overlying strata increases gradually after slice mining. The shear displacement of the overlying strata is in the shape of "W" after the lower seam mining, and the maximum shear displacement of the overlying strata by the lower seam mining is 1.67 times of that of the overlying strata after the upper seam mining. Field test of shear movement of the overlying strata was conducted on the panel 4308 of Chengzhuang coal mine. The results show that the shear displacement of the overlying strata above the coal seam increases with the burial depth. And the shear displacement of the overlying strata movement after mining has "time‐delay" effect. The larger the depth of the measuring point is, the larger value of the along‐strike shear displacement is. The breakage of the key strata of the overlying strata will cause the shear displacement of the overlying strata to increase rapidly. And there is a demarcation depth (127.98 m) for the shear displacement of the overlying strata. The shear movement of the overlying strata above the dividing point is not obvious, while the shear movement of the overlying strata below the dividing point is in the shape of "S" (amplitude of 50 mm). When the working face advanced beyond the test well, the overlying strata would experience multiple shear movement. When the working face advanced 34‐100 m ahead of the surface test well, the overlying strata experienced the most severe shear displacement. When the working face advanced to 74 m away from the surface test well, the shear displacement of the overlying strata between 10# (depth of 192.01 m) and 16# (depth of 300.07 m) is larger than that at the upper position, and down‐dip shear displacement is the most severe(about 315 mm). The shear displacement of the overlying strata is coincident with the along‐strike shear displacement, and the down‐dip shear displacement is smaller than the along‐strike shear displacement. This research provides theoretical guidance for the design of shale gas or coalbed methane surface wells and coal mine shaft under slice mining. Abstract : The shear movement of overlying strata by slice mining mainly shows "increase → decrease →increase → decrease." The shear displacement curve of overlying strata forms a "W" shape after lower seam mining. The maximum shear displacement of overlying strata by the lower seam mining is 1.67 times of that of overlying strata by the upper seam mining. The shear displacement of the strata above the coal seam increases with the burial depth. The farther the working face is from the test well, the smaller the shear displacement of overlying strata is.